2020
DOI: 10.7150/ijbs.45457
|View full text |Cite|
|
Sign up to set email alerts
|

Long noncoding RNA LINC01123 promotes the proliferation and invasion of hepatocellular carcinoma cells by modulating the miR-34a-5p/TUFT1 axis

Abstract: Hepatocellular carcinoma (HCC), one of the main causes of cancer-related deaths globally, is characterized by rapid growth and high invasiveness. Accumulating evidence demonstrates that long noncoding RNAs (lncRNAs) play critical roles in the growth and metastasis of HCC. Recently, lncRNA LINC01123 has been found to contribute to cell proliferation and aerobic glycolysis in lung cancer. However, the function of LINC01123 in HCC, as well as the underlying mechanism of its action, remain unclear. Here, we found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 33 publications
1
22
0
Order By: Relevance
“…The dysregulation and dysfunction of lncRNAs participate in the initiation and progression of HCC [25]. For example, lncRNA LINC01123 is overexpressed in HCC, and its overexpression predicts poor prognosis of patients [16]. LINC01123 facilitates the proliferation, migration, and invasion of HCC cells via miR-34a-5p/TUFT1 pathway [16].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The dysregulation and dysfunction of lncRNAs participate in the initiation and progression of HCC [25]. For example, lncRNA LINC01123 is overexpressed in HCC, and its overexpression predicts poor prognosis of patients [16]. LINC01123 facilitates the proliferation, migration, and invasion of HCC cells via miR-34a-5p/TUFT1 pathway [16].…”
Section: Discussionmentioning
confidence: 99%
“…For example, lncRNA LINC01123 is overexpressed in HCC, and its overexpression predicts poor prognosis of patients [16]. LINC01123 facilitates the proliferation, migration, and invasion of HCC cells via miR-34a-5p/TUFT1 pathway [16]. LncRNA A1BG-AS1 is a tumor-suppressive factor in HCC and functions as a miR-216a-5p sponge to suppress cancer cells' proliferation and invasion [26].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our paper 1 , the image of invaded Hep3B cells with empty vector transfection in Figure 3D was mis-pasted. Through repeated confirmation, we captured the images of invaded Hep3B cells with control siRNA or empty vector transfection at the same time and confirmed that we attached the same image of invaded Hep3B cells (control group) in Figure 2D and Figure 3D due to the negligence.…”
mentioning
confidence: 98%